KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS Vll SMP NEGERI 20 KUPANG TAHUN AJARAN 2025/2026 - Bernadeta Beo; Semuel H. Nitbani; Dian Sari Arindah Pekuwali (STKIP Subang, 2026)
The focus of this study is “How is the ability of seventh-grade students at SMP Negeri 20 Kupang in writing news texts?”. The aim of this research is to analyze and describe the students’ ability in writing news texts. The study is grounded in writing theory. A descriptive qualitative method was employed, using a performance-based test in which 27 students of Class VII-A were asked to write a news text. In this research, the material focused on news texts by paying attention to their structure and linguistic features. A news text is a type of text that reports on events or incidents that are currently happening and widely discussed by the public. Based on the analysis of the 27 students in Class VII-A of SMP Negeri 20 Kupang, their ability to write news texts, particularly in terms of structure and linguistic aspects, can be categorized as fairly good. This is supported by the completion rate: 20 students (74.1%) met the expected criteria, while 7 students (25.9%) did not.